Long‐term rice–crayfish farming aggravates soil gleying and induced changes of soil iron morphology. (23rd December 2020) - Yuan, Pengli; Wang, Jinping; Li, Chengfang; Cao, Cougui
Abstract: The integrated rice–crayfish (RC) farming has become popular in rice‐growing areas in China. In order to raise crayfish in paddy, the RC system requires large amounts of feed and flooding of fields, and changes in the use and management of paddy may have an impact on soil properties. This study investigated the effects of feed placement and long‐term flooding on soil profile structure, organic carbon, total nitrogen, total phosphorus, total potassium, redox status and iron oxides during RC farming. A series of paddy soil profiles from rice–crayfish paddies were sampled. Samples from adjacent paddies with rice monoculture (RM) were used for comparison. Soil samples from each paddy field were collected vertically every 20 cm from surface to a depth of 1 m. Our research indicated that the thicknesses of the gley horizons and concentrations of total nitrogen, total phosphorus, total potassium, soil organic carbon, total amount of reductive mater, active reducing matter, ferrous iron, divalent manganese, oxalate‐extractable iron (Feo ), and pyrophosphate‐extractable iron (Fep ) increased with the duration of RC farming. Conversely, Eh, and dithionite‐extractable iron (Fed ) content significantly decreased with time. In comparison with RM, the longer RC system lasts, the more severe gleying of the surface soil occurs, and the depth of gley extends downwards in the soil profile. Particularly thickened gleization layer, high content of organic nutrients, presence of reducing substances, low Eh value, and changes of soil iron minerals which affect soil fertility can predictably worse the function of the rice paddy environment and ecosystems.